1987
DOI: 10.1002/mrm.1910050606
|View full text |Cite
|
Sign up to set email alerts
|

An MRI phantom material for quantitative relaxometry

Abstract: Most phantom media in current use exhibit T1 relaxation times that are significantly dependent on both temperature and operating frequency. This can introduce undesirable variability into relaxation measurements due to temperature fluctuations, and complicates direct comparison of imagers operating at different magnetic field strengths. Our investigations of a nickel-doped agarose gel system have demonstrated near independence of the proton relaxation rates to a wide range of temperatures and frequencies. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 23 publications
2
87
0
Order By: Relevance
“…Phantoms of 2% (w/v) agar dissolved in nanopure (distilled and deionized) water, 0.01% (w/v) NaCl and various molar concentrations of gadopentetate dimeglumine (Gd-DTPA) were created in 50-mL centrifuge tubes. First, the agar powder was dissolved in 50 mL of nanopure water at 55-60 C and heated until 85 C for 5 min on a combined hotplate/magnetic stirrer until the solution became clear (19)(20)(21). Following the addition of NaCl, Gd-DTPA (MagnevistV R ) was then added at concentrations ranging from 0 to 2.0 mM (v/v) per tube to alter T 1 relaxivity and stirred for one minute.…”
Section: Tissue Modelmentioning
confidence: 99%
“…Phantoms of 2% (w/v) agar dissolved in nanopure (distilled and deionized) water, 0.01% (w/v) NaCl and various molar concentrations of gadopentetate dimeglumine (Gd-DTPA) were created in 50-mL centrifuge tubes. First, the agar powder was dissolved in 50 mL of nanopure water at 55-60 C and heated until 85 C for 5 min on a combined hotplate/magnetic stirrer until the solution became clear (19)(20)(21). Following the addition of NaCl, Gd-DTPA (MagnevistV R ) was then added at concentrations ranging from 0 to 2.0 mM (v/v) per tube to alter T 1 relaxivity and stirred for one minute.…”
Section: Tissue Modelmentioning
confidence: 99%
“…The Ni 2+ concentration in the stock solution was 5.3 mM, which should result in a T 1 relaxation time of approximately 300 ms (Morgan and Nolle 1959). The use of agarose gel instead of an aqueous solution shortens T 2 but should not affect T 1 (Kraft et al 1987). The polyvinylacetate and ink concentrations were 4% and 1% respectively.…”
Section: Influence Of Optical Dopants On Mr Images and Relaxation Timesmentioning
confidence: 99%
“…Therefore, a phantom that behaves similarly to human soft tissue functions as a replacement. The optimal characteristics of MRI phantoms used for such purposes are as follows: (1) relaxation times equivalent to those of human tissues, (2) dielectric properties equivalent to those of human tissues, (3) the relaxation times and dielectric properties should be homogeneous throughout the phantom, (4) mechanical properties suitable for fabrication of a human torso without the need for reinforcement, (5) can be used to form shapes of human organs, (6) ease of handling, and (7) stability of physical and imaging properties over an extended period. 1 Over the last few decades, several studies have been conducted on water-based polymer gels with paramagnetic ions as potential materials for MRI phantoms.…”
Section: Introductionmentioning
confidence: 99%
“…The T 1 and T 2 relaxation times represent the rate at which the longitudinal and transverse components of the magnetization vector of human tissue return to thermodynamic equilibrium. Some polymer gels that have been investigated include agarose, 2-4 agar, 5,6 polyvinyl alcohol, 7 gelatin, 8 and polysaccharide gels TX-150 9 and TX-151. 10 These studies have demonstrated that each material has potential for phantom application, but this is limited due to fragility and storage conditions.…”
Section: Introductionmentioning
confidence: 99%